Pengembangan Media Pembelajaran Berbasis Android pada Materi Suhu dan Kalor untuk Meningkatkan Minat Belajar Siswa Kelas XI - Rahmawati, Siti; Firdaus, Thoha; Mardova, Liyana (U-Teach: Journal Education of Young Physics Teacher, 2025)
The purpose of this study was to produce android-based physics teaching materials using MIT App Inventor that are feasible to use and can increase students' interest in learning MA Pondok Pesantren Sabilil Muqorobin Suka Agung using android-based application teaching materials on temperature and heat material. This research was conducted using the (Research and Development) method. The development model used refers to the ADDIE development model, namely (analysis, design, development, implementation, evaluate). The final product produced has met the validity criteria with an average score from the Material Expert Feasibility Test getting a percentage of 88.22%, Very valid qualifications, and very feasible feasibility criteria, and the media expert feasibility trial getting a value of 86.66%, Very valid qualifications, and very feasible feasibility criteria. Based on the results of student responses to the trial of Android-based application learning media obtained a percentage of 87.09% and stated high so that it can increase students' interest in learning after using Android-based learning media. It is expected that further researchers can create offline-based learning media. So that it can be accessed by students and teachers offline